(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In the article the element of psychology-pedagogical techniques direct and indirect infiuence on the specifics of emotional maturity of the pupils during the Ukrainian lessons i presented. The author brings that under the condition of introduction such kind of work for fhe children of the 5 or 6 forms the commnicative habis, are improved disappears the effort, fhe uneasy. The children become frank and sure, they express their ideas free. With a help of expressive psychological techniques the children take the new impressions and social experience.